Physical load control and prescription during resistance suspension strap training - Rojas-Valverde, Daniel; Gutiérrez-Luna, Dylson; Fallas-Campos, Andrea; Azofeifa-Mora, Christian (VIREF Revista de Educación Física, 2020)
The strap suspension training is a well-known and practiced resistance training methods. Despite its frequent use, there is lack of methods of control and prescription of the loads (e.g. intensity and volume) during exercising with this device and method. The aim of the present study was to propose a new practical approach in the control and prescription of physical load during resistance suspension strap training considering basic terminology. In suspension training with straps, setting the exercise using different subjection point height, rope length, distance from subjection point and attack angle could change both the intensity and the volume of the load. Considering the above, this information should be addressed by human science professionals, athletes and coaches in the designing and execution of conditioning and training programs using this method of suspension training, in order to make an optimal approach to a more individualized prescription. Likewise, the calculation and the use of attack angles and their variations together with the Suspension Training Total Resistance Load values give the possibility of making a more objective approach for the determination of an adequate training load, which based on the client's perception, could allow practitioners to generate a beneficial overload and obtain greater physical and physiological improvements.